Pengaruh Motivasi Keluarga Terhadap Kemampuan Kognitif Anak Usia 5-6 Tahun: Studi Masa Pandemi - Afsari, Fanny; Rusdiyani, Isti; Khosiah, Siti (Program Studi Pendidikan Islam Anak Usia Dini, Fakultas Ilmu Tarbiyah dan Keguruan, UIN Sunan Kalijaga, Yogyakarta, 2021)
During the pandemic, children aged 5-6 years need time to learn from home so that cognitive abilities during the pandemic experience obstacles. Family motivation has an important role in empowering children's cognitive abilities. The purpose of this study was to determine the effect of family motivation on the cognitive abilities of children aged 5-6 years during the pandemic. The research method used is quantitative. The research subjects found 60 children consisting and 60 parents of: grades B1, B2, B3, B4 at the Putera Bhineka Institute. Data collection techniques using observation, questionnaires, and documentation. The validity and reliability test showed that all the item instruments used were valid and reliable. Data analysis using SPSS 22.0 with simple linear regression test based on hypothesis testing. The results showed that there was no significant effect of motivation on children's cognitive abilities during the pandemic aged 5-6 years. The results of calculations with simple linear regression analysis and hypothesis testing can be said that tcount is 1.311 and a significance value is 0.195. The significant value is 0.195 > 0.05 or seen in the tcount of 1.311 < ttable 2.001. These results can be influenced by environmental factors in the community and the school environment. The findings of this study contribute that during the pandemic, children's cognitive abilities are not influenced by family motivation, but rather by environmental and other factors.